Implementation of Halal Supply Chain in the Cooperative of Islamic Boarding School: Maqashid Syariah Perspective - Siti Aminah Chaniago, Siti Aminah Chaniago; Muhammad Izza, Muhammad Izza; Bagaskara Sagita Wijaya, Bagaskara Sagita Wijaya; Feni Fitriani Putri Rozi, Feni Fitriani Putri Rozi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Halal Supply Chain is an opportunity, especially for countries with a majority Muslim population, including Indonesia, to increase the competitiveness of national products in a global context. Islamic boarding schools as centers for the development of Islamic law, also have the opportunity to create and apply Halal Supply Chain principles in the business units they develop. This research examines the application of Halal Supply Chain principles in Islamic boarding school cooperative business units that are integrated with Maqashid Syariah principles and their impact on business sustainability. This qualitative research was conducted at the